2022
DOI: 10.1177/10775595211069923
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Postneonatal Infant Mortality Associated With Prior Founded Allegations of Child Abuse

Abstract: This study examined the association between prior reports of child abuse and subsequent postneonatal death and differences by cause of death, using data from the Chicago Infant Mortality Study (CIMS). CIMS included all sudden, unexplained infant deaths up to 1 year of age in Chicago (November 1993-April 1996), and age, race-ethnicity and birthweight-matched living controls. Information on prior child abuse reports and outcomes was obtained through the Illinois Department of Children and Family Services (DCFS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Research on maltreatment has often focused on risk factors for serious injury and death. Hauck et al (2022) extend our understanding of the strong association between prior CPS reports and child fatality (Batra et al, 2021) by examining postneonatal death and differences by cause of death. Using data from the Chicago Infant Mortality Study (CIMS) that linked all sudden, unexplained infant deaths in Chicago with report data from the Illinois Department of Children and Family Services (DCFS) State Central Registry, they found that families known to DCFS were almost 4 times more likely to have a child die during the postneonatal period.…”
Section: Biology Risk Factors and Behaviormentioning
confidence: 97%
“…Research on maltreatment has often focused on risk factors for serious injury and death. Hauck et al (2022) extend our understanding of the strong association between prior CPS reports and child fatality (Batra et al, 2021) by examining postneonatal death and differences by cause of death. Using data from the Chicago Infant Mortality Study (CIMS) that linked all sudden, unexplained infant deaths in Chicago with report data from the Illinois Department of Children and Family Services (DCFS) State Central Registry, they found that families known to DCFS were almost 4 times more likely to have a child die during the postneonatal period.…”
Section: Biology Risk Factors and Behaviormentioning
confidence: 97%